BREAKING BARRIERS IN MERDEKA CURRICULUM IMPLEMENTATION THROUGH CULTURALLY RESPONSIVE TEACHING - Annisa, Tiara Nurul; Sukriyah, Toyyibatul Mukminatus; Holifah, Holifah; yaqin, Muhammad Ainul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze the implementation of Islamic religious education in improving character by adapting teaching methods to the student's cultural context. This study uses qualitative methods with a case study at PDF Nurul Jadid Paiton Probolinggo, involving interviews, observation and documentation. The research results show that applying Islamic religious education can train students to have good character. Family involvement also contributes significantly to students' academic achievement and social development. Overall, using Islamic religious education has great potential in improving the development of students' good character development. This approach not only meets academic needs but also considers the social and emotional aspects of the student learning experience, as well as positively contributing to diversity and preserving local culture.